Photoluminescence and Raman Spectroscopy Studies of Carbon Nitride Films - J. Hernández-Torres; A. Gutierrez-Franco; P. G. González; L. García-González; T. Hernandez-Quiroz; L. Zamora-Peredo; V. H. Méndez-García; A. Cisneros-de la Rosa (Journal of Spectroscopy)
Amorphous carbon nitride films with N/C ratios ranging from 2.24 to 3.26 were deposited by reactive sputtering at room temperature on corning glass, silicon, and quartz as substrates. The average chemical composition of the films was obtained from the semiquantitative energy dispersive spectroscopy analysis. Photoluminescence measurements were performed to determine the optical band gap of the films. The photoluminescence spectra displayed two peaks: one associated with the substrate and the other associated with CNx films located at ≈2.13±0.02 eV. Results show an increase in the optical band gap from 2.11 to 2.15 eV associated with the increase in the N/C ratio. Raman spectroscopy measurements showed a dominant D band. ID/IG ratio reaches a maximum value for N/C ≈ 3.03 when the optical band gap is 2.12 eV. Features observed by the photoluminescence and Raman studies have been associated with the increase in the carbon sp2/sp3 ratio due to presence of high nitrogen content.